Shared Surgical Decision Making and Youth Resilience Correlates of Satisfaction With Clinical Outcomes. Issue 5 (July 2015) - Kapp-Simon, Kathleen A.; Edwards, Todd; Ruta, Caroline; Bellucci, Claudia Crilly; Aspirnall, Cassandra L.; Strauss, Ronald P.; Topolski, Tari D.; Rumsey, Nichola J.; Patrick, Donald L.
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to identify factors associated with youth satisfaction with surgical procedures performed to address oral cleft or craniofacial conditions (CFCs). It was hypothesized that youth mental health, participation in decision making, perceived consequences of living with a CFC, and coping strategies would be associated with satisfaction with past surgeries. A total of 203 youth between the ages of 11 and 18 years (mean age = 14.5, standard deviation = 2.0, 61% male participants, 78% oral cleft) completed a series of questionnaires measuring depression, self-esteem, participation in decision making, condition severity, negative and positive consequences of having a CFC, coping, and satisfaction with past surgeries. Multiple regression analysis using boot-strapping techniques found that youth participation in decision making, youth perception of positive consequences of having a CFC, and coping accounted for 32% of the variance in satisfaction with past surgeries (P < 0.001). Youth age, sex, and assessment of condition severity were not significantly associated with satisfaction with surgical outcome. Depression, self-esteem, and negative consequences of having a CFC were not associated with satisfaction with past surgeries. Youth should be actively involved in the decision for craniofacial surgery. Youth who were more satisfied with their surgical outcomes also viewed themselves as having gained from the experience of living with a CFC. They felt that having a CFC made them stronger people and they believed that they were more accepting of others and more in touch with others' feelings because of what they had been through.